Pendekatan Regresi Logistik Pada Perataan Laba - Sully Kemala Octisari; Minadi Wijaya; Aisyah Ayu Baroroh (Universitas Batanghari Jambi, 2021)
Earnings management is one of the management actions for engineering company performance. The act of engineering profit can be said to be legal by some parties. There are many ways to do earnings management, one of which is income smoothing. This researcher aims to analyze the profitability of income smoothing in the metal industry and the like in 2011-2018. In this study using logistic regression using a dummy. The results of this study indicate that profitability and firm size do not have a significant effect on income smoothing, while financial leverage has a significant effect on income smoothing. The implication of this research is that 1) the company's efforts to attract investors do not have to focus only on profitability and company size 2) the company must pay attention to the ratio between the company's liabilities and the company's assets.